Kepastian Hukum Pemegang Hak atas Tanah dalam Sistem Hukum Pertanahan di Indonesia - I Made Citra Gada Kumara; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Warmadewa Press, 2021)
Land rights certificates still face the possibility of lawsuits from other parties who feel they have rights to the land, so that if it can be legally proven that he is the real owner, the land rights certificate can be canceled. The purpose of this study is to determine the legal certainty of land rights holders in the land law system in Indonesia and the government's efforts to provide legal certainty to land rights holders. The type of research used in this research is normative legal research. Sources of data used are primary and secondary data sources. The technique of collecting legal materials is done by recording, studying and reading legal doctrines related to the legal issues under study. The legal material analysis technique used to process the legal material obtained is by using analytical descriptive data analysis. The results of the study indicate that the evidentiary strength of a certificate of land rights owned by the right holder is basically guaranteed by law because it is written clearly about the types of rights, physical information regarding the land, the burden on the land and legal events that are interconnected with the land. then the data is considered correct